Workplace Communication during the Pandemic situation - Rajesh, Nalini; Kanagalakshmi, Dr. L (The journal of contemporary issues in business and government, 2022)
Workplace communication plays an important role in the successful implementation of any project. During the pandemic, disruption had happened not only in operations but in the front of communication too. Modern organizations have very different kind of crisis (Fink, 1986; Perrow, 1984; Bozeman,2011) The covid19 pandemic had created a great havoc on the normal life and its impact on organizations had been huge including negatives changes in productivity. Mazzei, Kim and Dell‟Oro (2012) is of the opinion that it is important for an organization to build trust within the organization during the crisis as this would ensure good relationship, enhanced productivity and better finance. This research had adopted the case study methodology to bring forth the communication challenges during covid19 in a manufacturing organization. Silliconnect, a supply chain solutions company had been following rigorous quality improvement methods. Employee awareness on issues related to quality was provided periodically as it determines the success of the quality journey (Anithakumari & Gayathri, 2018). This is a fictitious case study, designed for class room teaching on the concept of workplace communication during crisis.